An Information-Centric Framework for Designing Patient-Centered Medical Decision Aids and Risk Communication - Franklin, Lyndsey (American Medical Informatics Association, 2013)
Risk communication is a major challenge in productive patient-physician communication. Patient decision making responsibilities come with an implicit assumption that patients are sufficiently educated and confident in their abilities to make decisions about their care based on evidence based treatment recommendations. Attempts to improve health literacy in patients by way of graphical decision aids have met with success. Such decision aids typically have been designed for a general population and evaluated based on whether or not users of the decision aid can accurately report the data points in isolation. To classify decision aids, we present an information-centric framework for assessing the content delivered to patients. We provide examples of our framework from a literature survey and suggest ways improvements can be made by considering all dimensions of our framework.